2016
DOI: 10.1080/09603123.2015.1135312
|View full text |Cite
|
Sign up to set email alerts
|

Presence of human noroviruses on bathroom surfaces: a review of the literature

Abstract: Enteric viruses are the most common cause of acute gastroenteritis worldwide with most cases of illness attributed to caliciviruses, such as human noroviruses (HuNoV). While environmental transmission of HuNoV is reported to be low, environmental surfaces could be a source of secondary transmission. As many vomiting/fecal episodes occur in bathrooms, bathroom surfaces could be an important vehicle for transmitting HuNoV. We systematically reviewed the literature to determine the presence of HuNoV on bathroom s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Most norovirus-positive samples came from the underside of the toilet seat, followed by the toilet flush handle, inner door handle, and the sink faucet. Leone et al (36) found similar results in their literature review of the presence of human norovirus on bathroom surfaces. Norovirus-positive samples were found on toilet seats in five studies (9, 15, 19, 34, 64) and on sink faucet handles (15, 22, 23), toilet flush handles (48), and bathroom door handles (22, 34, 48) in fewer studies.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Most norovirus-positive samples came from the underside of the toilet seat, followed by the toilet flush handle, inner door handle, and the sink faucet. Leone et al (36) found similar results in their literature review of the presence of human norovirus on bathroom surfaces. Norovirus-positive samples were found on toilet seats in five studies (9, 15, 19, 34, 64) and on sink faucet handles (15, 22, 23), toilet flush handles (48), and bathroom door handles (22, 34, 48) in fewer studies.…”
Section: Discussionmentioning
confidence: 53%
“…Norovirus was present on 1.5% of bathroom surfaces sampled in this study, which is consistent with the 1.7 and 1.9% prevalence reported in The Netherlands in 2011 and 2015, respectively (10, 11). In a recent systematic review of seven articles published from 1980 to 2014 (36), only three included reports of norovirus-positive samples from bathroom surfaces in commercial and institutional settings under nonoutbreak conditions (10, 48, 61). One reason for the low prevalence in our study could be that human norovirus was present in such low numbers that they were below the limit of detection of our multiplex real-time RT-PCR (13) assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful and detailed epidemiological studies are required to link toilet use with infection incidence. This has been done for norovirus, during air and boat travel, and restaurant visits, where confirmed cases using the bathroom/toilet were linked with norovirus acquisition (Boxman et al, 2009;Carling et al, 2009;Chimonas et al, 2008;Ho et al, 1989;Jones et al, 2007;Leone et al, 2016;Widdowson et al, 2005). Other pathogenic viruses have been associated with toilets in offices and hospital, with the most contaminated surfaces reported as bathroom door handles (66%), flushing buttons (62%), toilet seats (59%), and toilet covers (52%) (Verani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one review identified six studies that implicated bathroom surfaces as primary sources of human norovirus infection. 7…”
Section: Introductionmentioning
confidence: 99%